An Electric DC Motor Control System with Geckodrive320x Driver Module - Agus Hananto; Rachmad Hartono; Ahid Nuristinah (Jurnal Metal Indonesia, 2020)
This research shows an example to make a servo motor which consists of three main components, a DC motor, a control circuit, and a closed feedback system. A rotary encoder is used as a closed feedback system by using Geckodrive320X as a control circuit for controlling DC electric motors as the main components. The results showed that Geckodrive320X can be used to control a DC electric motor as a servo motor. The number of turns of the DC motor shaft depends on the condition of switches SW2 and SW3, achieved by giving four pulses to the Geckodrive320X. The maximum speed able to be controlled by Geckodrive320X is 540 rpm, and the deviation maximum of the slider positioning is 0.01 mm under the conditions of multipliers of 5 and 10.